Optimization of the perfect absorber for solar energy harvesting based on the cone-like nanostructures - Zhaolong Wang; Guihui Duan; Huigao Duan (AIMS Energy, 2021)
The effects of materials, geometric parameters, and morphologies on the absorption properties of absorbers with the cone-like nanostructures surrounded by water have been numerically studied. The underlying mechanisms of the perfect absorption of solar energy are revealed by gradient index effect with electric field distributions. It shows that the absorber achieves perfect absorption for solar energy harvesting with nanocones made of Chromium (Cr), Nickel (Ni), Platinum (Pt), Titanium (Ti), and Bismuth Telluride (Bi2Te3), while the perfect absorption wavelength region of absorbers with nanocones made of noble metals (Au, Ag) is 300 nm to around 650 nm, which is far narrower than the solar spectrum. In addition, geometric parameters of the nanocones on the surface of the metamaterials make a big difference on the absorption properties of them though there is a small tolerance. Besides, the morphology of the cone makes a little difference on the absorption properties of the absorber, and the absorptance of the absorber increases with the increase of the number of nanocone's sides. Furthermore, the solar absorber with nanocones is sensitive to the incident angle of the light with a small tolerance, but the polarization of the incident light almost makes no difference on the absorption property of the absorber with nanocones.